Compact microstrip bandpass filter - Said, Faridah (2014)
In microwave communication systems, the bandpass filter is an essential component, which is usually used in both transmitter and receiver. Parallel-coupled microstrip bandpass filter is one of the most popular filters in communication systems. However, this arrangement of parallel-coupled microstrip bandpass filter gives disadvantage in terms of size where the arrangement of this topology results in an electrically large in size of the filter. Therefore, this project focuses on designing a compact microstrip bandpass filter by using Sonnet Lite software software at centre frequency of 3.2GHz with the bandwidth of 400MHz. Besides, the design of the compact microstrip bandpass filter has achieved the objective when it successfully reduced the overall size to about 70% as compared to the size of conventional filter, which is parallel-coupled microstrip bandpass filter. Both filters give the same performance based on their frequency responses. The design also has successfully fabricated and measured by using network analyzer software to verify the simulated results obtained earlier. Although there is slightly mismatch between the simulated and measured frequency response due to some fabrication errors and variation of material properties, the design of filter is not affected since the results obtained from the designing process by using Sonnet Lite software are still valid and can be used in future improvement of the design.